Exploring Local Managers’ Motivations to Seek Problem-Solving in Response to Citizens’ Feedback Signals on Service Quality - Heontae Shin; Youngmin Oh (Transylvanian Review of Administrative Sciences, 2022)
Performance management has become a global trend in government reform movements. Previous studies have emphasized performance feedback, referring to the fact that local governments have adopted numerous performance practices to enhance local service performance. Accordingly, while many studies sought mechanisms that motivate managers to seek performance feedback, they have not clarified how the different performance information signals foster managers’ problem-solving activities. This study conducted a survey experiment to assess local managers’ agreement with a problem-solving system such as performance consulting when presented with the performance information on citizen satisfaction with service quality. The results indicate that local managers with low citizen satisfaction scores are more reactive to the performance information, supporting problem-solving system, and the managerial reactions to performance information increase with detailed information.